Promoting the System of Educational Quality Management in an Indonesian Madrasa - Munjin Munjin; M. Sugeng Sholehuddin (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2019)
Despite being widely investigated in the realm of educational institutions, quality management along with quality assurance in a madrasa setting receives scanty attention. To fill this gap, the present study attempts to showcase design and implementation of educational quality management performed in a public primary madrasa situated in Yogyakarta, Indonesia. It looks at quality assurance in character building, educational management, teaching and learning processes, and human resources management in this madrasa. Grounded in a qualitative case study, in-depth interviews with the madrasa principal and head of student affairs as well as observation were carried out to garner data. The findings of the study demonstrated that the madrasa designed stages of quality management, namely: planning, organizing, mobilizing, supervising, developing, and evaluating. The implementation of this design used bottom-up, transparent, and accountable system, accompanied by a clear job description in each position so that it provided optimal education services. Additionally, the quality assurance coped with character building, internal and external audit, teaching and learning innovations, and quality development of the teacher and academic staffs. The study also promoted that this madrasa designed the concept of children-friendly school aiming to provide a comfortable learning environment for all the madrasa members.